Adolescent Substance Abuse Treatment: Does Family Systems Therapy Improve Family Functioning and Decrease Drug Use? - Wallis, Darin J. (2013)
Family systems therapy is a way of working with individuals, couples, families, or a group of people that emphasizes relationships and a person's/family's greater system as important factors in establishing change and health (Haley, 1976; Minuchin, 1974). Treating adolescent substance abuse with family systems therapy has been demonstrated in the literature as being an effective method of intervention (Coatsworth, Santisteban, McBride, & Szapocznik, 2001; Kumfer & Alvarado, 2003; Leichtling, Gabriel, Lewis & Vander Ley, 2006; Liddle, 2002; Liddle et al., 2001; Rowe & Liddle, 2003), as the various ecological and epidemiological factors associated with adolescent substance abuse can be addressed effectively with family systems work (Cunningham & Henggler, 1999; Kaufman & Kaufman, 1979; Liddle et al., 2001; Szapocznik & Williams, 2000). The dissertation used a sample of 71 families who participated in a family systems therapy intensive outpatient substance abuse program in the greater metro-Denver area from 2006 to mid-2008. The youth, aged 13-17 years old, tended to be highly involved with substance abuse, were not motivated to change, and were not interested in participating in treatment. A three-month follow-up survey was evaluated and demonstrated that both youth and parents/guardians found that that family systems therapy was effective in increasing the family's functioning, decreasing the youth's substance use, increasing the youth's school performance, and decreasing the youth's court involvement